The Influence of Digital Technology Utilization on Motivation and English Language Learning Ability: a Systematic Literature Review - Akmir Akmir; Ayla Putri; Syaefi Ramadhani; Suci Pratiwi; Agista Cahyani; Annisa Annisa (Invention: Journal Research and Education Studies, 2026)
The rapid development of digital technology has brought substantial changes to educational practices, particularly in English as a Foreign Language (EFL) learning. This study aims to examine the utilization of digital technology in English learning and analyze its influence on students’ learning motivation and English language abilities. This research employed a qualitative field research approach. Data were collected through classroom observations, semi-structured interviews with English teachers and seventh-grade students, and documentation of digital-based learning activities. The findings indicate that the integration of digital technology such as learning videos, interactive quizzes, and digital visual media positively influences students’ motivation by increasing engagement, participation, and learning enjoyment. In addition, digital technology supports the development of students’ English language abilities, particularly vocabulary mastery and reading comprehension. However, several challenges were identified, including limited instructional time, differences in students’ digital competencies, and teachers’ readiness to integrate technology effectively. Therefore, the successful implementation of digital technology in EFL learning requires careful instructional planning, teacher professional development, and institutional support.